Oral tablet formulations containing cyclodextrin complexes of poorly water soluble cefdinir to enhance its bioavailability - DURMUŞOĞLU, LÜTFİYE (ELSEVIER, 2020)
Cefdinir (CFD) is an oral cephalosporin antibiotic commonly used in the treatment of community-acquired infections. The oral bioavailability of CFD is limited due to its poor aqueous solubility. Cyclodextrins (CyDs) and their chemically modified derivatives are used in the pharmaceutical field to form inclusion complexes with drug molecules to improve their aqueous solubility as well as stability and to prevent side effects. In this study, CFD was complexed with CyDs such as beta-cyclodextrin (beta-CyD), gamma-cyclodextrin (gamma-CyD), hydroxypropyl-beta-cyclodextrin (HP-beta-CyD), and sulphobutyl ether 7-beta-cyclodextrin (SBE7-beta-CyD) to increase its aqueous solubility and to reduce its side effects without decreasing the antimicrobial activity. Phase solubility studies were performed and the stability constant of the CFD:CyD inclusion complexes was determined. The solubility of CFD was increased after complexation with CyDs as indicated by phase solubility studies, in the order beta-CD < HP-beta-CyD < gamma-CyD < SBE7-beta-CyD, a result that depends on the conditions of complexation formation. Complex formation between CFD and CyDs was evaluated using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and powder x-ray diffractometry (PXRD) studies. The antimicrobial activity of the complexes against Staphylococcus aureus and Escherichia coli strains were evaluated and the strains showed higher susceptibility to CFD:HP-beta-CyD complex. Oral tablet formulations were fabricated using Avicel (R) PH 102 or Ludipress (R) as direct compression agent and magnesium stearate as lubricant. Using CFD:HP-beta-CyD complex in tablets significantly improved the dissolution rate of the drug when compared with that of formulation containing CFD alone.
Keywords: Cyclodextrin; Cefdinir; Inclusion complex; Drug solubility; Oral drug delivery; Tablet; HYDROXYPROPYL-BETA-CYCLODEXTRIN; INCLUSION COMPLEX; PHYSICOCHEMICAL PROPERTIES; ANTIMICROBIAL ACTIVITY; SOLUBILIZATION; DRUG; ITRACONAZOLE; RELEASE; PH